Ancient Thouria Lagynos: An Organic Residue Case Study - Brink, Delaney Maud Lee (Πανεπιστήμιο Πελοποννήσου, 2022)
A lagynos vessel ascribed to Hellenistic Times from the Ancient Thouria archaeological site was found undamaged in a tomb that was uncovered during a rescue excavation. Based on the vessel type and appearance, it was assumed to have contained wine or oils which were presumably used in a funerary context. As the vessel was discovered in a rescue excavation, it is important to understand the context of the vessel in addition to its contents. In order to verify the identity of the vessel’s possible organic residue, archaeometric analysis was required. Due to the delicate and unique state of the lagynos, the archaeological soil inside of the vessel was analyzed in order to prevent damage to the vessel itself. The study was conducted through the use of minimally invasive optical microscopy, SEM-EDS, RAMAN spectroscopy, and FTIR spectroscopy. In order to evaluate the results, the archaeological soil was compared against reference soils collected from the Thouria area at various distances from the tomb. Based on the results of the analysis, it is assumed that there are organic remains inside of the vessel and that the vessel was unmoved post-deposition in the tomb until its rediscovery in 2018. Thus, it is the goal of this study to determine if archaeological soils can be utilized to verify the presence of organic remains without the destruction of intact ceramic bodies or potsherds fragments.
Λάγυνος της Αρχαίας Θουρίας: μια μελέτη περίπτωσης οργανικών καταλοίπων
Keywords: Κεραμική, Ελληνική -- Θουρία (Αρχαία πόλη); Αγγεία, Ελληνικά -- Θουρία (Αρχαία πόλη); Κεραμική -- Θουρία (Αρχαία πόλη) -- Ανάλυση; Κεραμική -- Ανάλυση; Οργανικές ενώσεις -- Ανάλυση; Κεραμική -- Τεχνική; Αρχαιολογία -- Μεθοδολογία -- Περιπτωσιολογικές μελέτες; Ανασκαφές (Αρχαιολογία) -- Θουρία (Αρχαία πόλη); Θουρία (Αρχαία πόλη) -- Αρχαιότητες; Thouria; Organic Residue; Lagynos; FTIR; Archeological Soil; Minimally Invasive; Θουρία; Οργανικά Κατάλοιπα; Λάγυνος; FTIR; Αρχαιολογικό Χώμα; Ελάχιστα Επεμβατική Μέθοδος